Tunable Terahertz Perfect-Absorbers With Dual Peak Based on Reverse Graphene Patch Metamaterials - Yifan Chen; Xusheng Pan; Zhiyu Bao; Yiqing Wang; Zheng-Da Hu; Jicheng Wang (IEEE Photonics Journal, 2021)
In this paper, we proposed a tunable graphene-based metamaterial absorber (MA) at dual terahertz band to achieve perfect absorption. The electric field intensity distributions of demonstrated structure is illustrated to explain the origin of two absorption peaks. Simulation result shows the proposed MA owning polarization-insensitive property and wide incident angle tolerance. An inversion algorithm is used to extract the equivalent impedance and explore the physical mechanism of multiple-peak absorption. The equivalent impedance is explored through algorithm when the Fermi energy level alters, consequently the variation of resonant frequency of corresponding absorption peak is determined. Simultaneously, the resonant frequencies of absorption peaks can be adjusted by changing the geometric parameters of the graphene. Furthermore, we adapt the proposed structure into reversely designed pattern, achieving similar characteristic of dual-band absorption peaks and tunability. Thus, our work provides new insight and useful design guidance to various tunable multiple band terahertz metamaterial perfect-absorbers.